Randomized Comparison of High-Sensitivity Troponin Reporting in Undifferentiated Chest Pain Assessment. (September 2016) - Chew, Derek P.; Zeitz, Christopher; Worthley, Matthew; Grantham, Hugh; Beltrame, John; Arstall, Margaret; Coates, Penelope; Astley, Carolyn; Quinn, Stephen; Ratcliffe, Julie; Horsfall, Matthew; Aylward, Philip G.
Abstract : Background—: High-sensitivity troponin T (hs-TnT) assays promise greater discrimination of evolving myocardial infarction, but the impact of unguided implementation on the effectiveness of care is uncertain. Methods and Results—: We evaluated the impact of hs-TnT reporting on care and outcome among chest pain patients presenting to 5 emergency departments within a multicenter randomized trial. Patients were allocated to hs-TnT reporting (hs-report) or standard reporting (std-report; Roche Elecys). The primary end point was death and new or recurrent acute coronary syndrome by 12 months. A total of 1937 patients without ST-segment elevation were enrolled between July 2011 and March 2013. The median age was 61 (interquartile range, 48–74) years, and 46.3% were women. During the index hospitalization, 1466 patients (75.7%) had maximal troponin <30 ng/L within 24 hours. Randomization to hs-report format did not alter the admission rate (hs-report: 57.7% versus std-report: 58.0%; P =0.069). There was no difference in angiography (hs-report: 11.9% versus std-report: 10.9%; P =0.479). The hs-reporting did not reduce 12-month death or new/recurrent acute coronary syndrome in the overall population (hs-report: 9.7% versus std-report: 7.2% [hazard ratio, 0.83 (0.57–1.22); P =0.362]). However, among those with troponin levels <30 ng/L, a modest reduction in the primary end point was observed (hs-report: 2.6% versus std-report: 4.4%, [hazard ratio, 0.58; 95% confidence interval, 0.34–0.1.00; P =0.050). Conclusions—: High-sensitivity troponin reporting alone is associated with only modest changes in practice. Clinical effectiveness in the adoption of high-sensitivity troponin may require close coupling with protocols that guide interpretation and care. Clinical Trial Registration—: URL:http://www.ANZCTR.org.au . Unique identifier: ACTRN12611000879965. Abstract : Supplemental Digital Content is available in the text.